2021
DOI: 10.1186/s12879-021-06745-w
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of tuberculosis in persons living with HIV in Eastern Europe: associated factors and effect on mortality—a multicentre prospective cohort study

Abstract: Background Early diagnosis of tuberculosis (TB) is important to reduce transmission, morbidity and mortality in people living with HIV (PLWH). Methods PLWH with a diagnosis of TB were enrolled from HIV and TB clinics in Eastern Europe and followed until 24 months. Delayed diagnosis was defined as duration of TB symptoms (cough, weight-loss or fever) for ≥ 1 month before TB diagnosis. Risk factors for delayed TB diagnosis were assessed using multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…In line with European data, in our cohort there is a slight prevalence of male subjects [ 10 11 ] and almost three-quarters of our cohort belonged to the younger group with a median age of 39 years; our study population is younger than would be expected in low TB burden countries in which the geriatric population represents a large reservoir of TB infection [ 12 13 ].…”
Section: Discussionsupporting
confidence: 86%
“…In line with European data, in our cohort there is a slight prevalence of male subjects [ 10 11 ] and almost three-quarters of our cohort belonged to the younger group with a median age of 39 years; our study population is younger than would be expected in low TB burden countries in which the geriatric population represents a large reservoir of TB infection [ 12 13 ].…”
Section: Discussionsupporting
confidence: 86%
“…The rate of miliary TB was 12.6% in new TB cases and 6.6% in previously treated TB cases and this form of TB was not associated with the poorer treatment outcome. In other large multicenter prospective studies [ 16 , 56 ], the rate of miliary TB was higher and the association with the increased risk of death was found. These differences could be explained by a larger number of participants and different stratifications used for analysis.…”
Section: Discussionmentioning
confidence: 86%
“…The assessment of TB treatment outcomes, analysis and prevention of factors associated with unsuccessful treatment results is of crucial importance in reaching the success in TB control programme. In the frame of WHO End TB Strategy [ 56 ], this study identified risk groups requiring integrated programmatic case management.…”
Section: Discussionmentioning
confidence: 99%
“…TB laboratories and TB wards were re-assigned to the fight against COVID-19, which also disrupted TB services due to late diagnosis and late initiation of treatment. Delayed diagnosis can lead to the worst outcomes and, in the case of communicable diseases like TB, increases the chances of household transmission [ 15 ].…”
Section: Discussionmentioning
confidence: 99%